On Growth of Meromorphic Solutions of Complex Functional Difference Equations - Jing Li (Abstract and Applied Analysis, 2014)
The main purpose of this paper is to investigate the growth order of the meromorphic solutions of complex functional difference equation of the form (∑λ∈I‍αλ(z)(∏ν=1n‍f(z+cν)lλ,ν))/(∑μ∈J‍βμ(z)(∏ν=1n‍f(z+cν)mμ,ν))=Q(z,f(p(z))), where I={λ=(lλ,1,lλ,2,…,lλ,n)∣lλ,ν∈ℕ⋃‍{0},  ν=1,2,…,n} and J={μ=(mμ,1,mμ,2,…,mμ,n)∣mμ,ν∈ℕ⋃‍{0},  ν=1,2,…,n} are two finite index sets, cν (ν=1,2,…,n) are distinct complex numbers, αλ(z) (λ∈I) and βμ(z) (μ∈J) are small functions relative to f(z), and Q(z,u) is a rational function in u with coefficients which are small functions of f(z), p(z)=pkzk+pk-1zk-1+⋯+p0∈ℂ[z] of degree k≥1. We also give some examples to show that our results are sharp.